Beckman Hypoxia Warning System - Beckman Instruments Photographic Services Section (1969)
This warning device used an oxygen sensor to monitor the breathing system in F-4 aircraft. It was developed for General Electric under contract 810-2050.
Keywords: Scientific apparatus and instruments; Oxygen--Measurement; Phantom II (Jet fighter plane); General Electric Company; Beckman Instruments, Inc.